Representations of Love and Gender Constructions in Song Lyrics: A Corpus Analysis of the Works of Dewa 19 and Raisa Andriana - Baiq Resti Rizanti; Titik Sudartinah (Jurnal Riset Komunikasi (JURKOM), 2026)
This study aims to reveal the representation of the word “love” and gender constructs in the lyrics of Dewa 19 and Raisa songs using the Corpus-Assisted Discourse Studies (CADS) approach. This study is a mixed, qualitative-descriptive study supported by quantitative corpus analysis. A total of 30 song lyrics containing the word “love” were analyzed using the AntConc tool through three main stages, namely word frequency analysis, collocation, and concordance to identify lexical patterns and discourse orientation that emerged. The results of the analysis show that Dewa 19's lyrics tend to frame love through language that affirms emotional dominance and masculine roles that direct relationships. In contrast, Raisa's lyrics present love as an affective experience that is nurtured through reflection and emotional closeness, thus forming a more egalitarian representation. These findings confirm that popular music plays a role as a space for the formation of social meanings related to gender relations and roles, while also encouraging the need for more empowering representations in Indonesian cultural discourse.